Helianthus annuus (Sunflower) Petal Extract as an Effective and Sustainable Natural Acid-base Indicator - Sani, Hassan; Kani, Uwaisu Nura; Agbekelyun, Risikat Ogunkemi; Badamasi, Abdullahi Ado (Sciences of Phytochemistry, 2026)
The search for a safe, low cost and environmentally friendly alternative to synthetic chemical indicators is the main goal in green analytical chemistry. This study investigated the potential of Sunflower petal extract as a natural acid-base indicator to replace phenolphthalein. The plant pigment was extracted using cold maceration with methanol. The extract was characterized yielding 29%, a pH of 6.51, a wavelength of 450 nm and melting point of 248–250ºC. It demonstrates a sharp color change from brown in acidic media to yellow in basic media. Its performance was evaluated against standard phenolphthalein in four titration types: strong acid versus strong base, strong acid versus weak base, weak acid versus strong base, and weak acid versus weak base. The average titre values for the sunflower extract are (25.65±0.00, 8.65±0.070, 16.16±0.070 and 6.65±0.00 mL) respectively, and were in close agreement with phenolphthalein values (26.65±0.07, 8.65±0.070, 16.05±0.070 and 5.65±0.07 mL). The highest deviation recorded was only 1.00 mL, indicating comparable accuracy and precision between the two indicators. Furthermore, the extract showed good stability under varying temperature and light exposure conditions, suggesting its strong suitability for routine laboratory use. The pigment responsible for the observed color transitions is believed to belong to the flavonoid group, which is known for its sensitivity to pH changes. These findings demonstrate that sunflower petal extract can serve as an effective natural indicator and an excellent replacement for synthetic phenolphthalein in educational and analytical titrimetry, considering its availability, distinct color transition, low toxicity, and overall environmental friendliness.